In vitro antibacterial efficiency of some herbal extracts and theirs blends against subclinical mastitis pathogens (S. aureus and E. coli) - Aydın, Hanifi (Progress in Nutrition, 2021)
Study Objectives: The current research will form the basis for the production of new herbal mastitis drugs as an alternative to antibiotics. In this context, the aim of the study was to evaluate the in vitro antibacterial activity of O. onites and O. sanctum essential oil, solutions prepared in fixed oils of N. sativa and O. europaea, against S. aureus and E. coli bacteria which are the main agents of mastitis. Methods: Microorganism isolation and antibiotic susceptibility analyzes of milk samples taken from 43 subclinical mastitis dairy cows were performed. The antibacterial properties of the solutions were analyzed by a disk diffusion method. Results: In the bacterial isolation results, S.aureus was determined 97.7% and E.coli 34.9% positive of cows with mastitis. Occur that extract of O. onites showed maximum inhibition against S. aureus (23 mm) and E. coli (15 mm). At the same time, E.coli, which is already known to be multi-resistant to drugs, was susceptible only to the extract from O.onites. When the mean ± SD zone areas for the susceptible solutions (C, C1, C2, O, S, O+S, and Z2) and the control group were compared, determined that there was no statistically significant difference for S.aureus and E.coli (p>0.05). Conclusion: It was determined that the effectiveness of olive oil as a solvent against S. aureus was not sufficient, therefore, a 50% solution (15mm zone diameter) with N. sativa fixed oil was more effective.